Sports practice as an educational process in developmental age: Educational models and practices for the transition from play to sport - Annoscia, Sabrina; Ladiana, Sara; Colella, Dario (Formazione & insegnamento, 2024)
The practice of sporting activities holds significant relevance within the educational process of each individual. Sport Pedagogy (SP) occurs in a variety of contexts, including schools, sports associations, and families. It encompasses physical education, teaching-learning process analysis, sports training studies, and sports policies. The aim of this contribution is to present the relationships between SP and Physical Literacy (PL) as prerequisites for methodological interventions that promote the transition from play to sport. Variation in teaching styles promotes different learning modes and non-linear teaching in learners through the proposal of open, transferable, and person-adapted tasks. PL through play fosters long-term physical activity participation and facilitates the transition from play to sport, provided it is well-supported methodologically. The Long Term Athletic Development (LTAD) model is also presented, emphasizing the fundamental role of the methodological approach.